(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Urbanization has resulted in a continuous escalation of land values and housing prices in urban regions, while the demand for residential units in cities persists in increasing. As a result, government-provided subsidized housing has become a crucial option for low-income communities. Nevertheless, these subsidized housing projects are frequently criticized for their insufficient construction quality. Growing concerns have emerged that such developments may unintentionally intensify global warming by elevating ambient temperatures within the residential environment. This study investigates how variations in building mass configuration and architectural form influence outdoor temperature as a passive design strategy to improve thermal conditions in subsidized housing areas. The analysis employs a hypothetical massing model of subsidized housing simulated using Rhinoceros, Grasshopper, and Ladybug. The results demonstrate that adjustments in building mass configuration and form are capable of lowering outdoor temperatures, although the impact remains relatively modest. Case Study 4B, which uses asphalt as the site’s surface material and represents the scenario with the most favorable UTCI values in both orientations, achieves a UTCI reduction of 1.8 °C for the West–East orientation and 1.6 °C for the North–South orientation when compared to the base case.